Association between estimated plasma volume status and the risk of 30-day mortality in patients with severe acute pancreatitis: a retrospective study based on the MIMIC-IV database - Haibo Zhang; Jiebin Li; Dawei Wang; Jing Wang; Lijun Duan; Jing Zhang (BMC Gastroenterology)
Abstract Background Assessing plasma volume is important in the management and treatment of severe acute pancreatitis (SAP). Although it is an easy and rapid method for estimating the plasma volume, the association between estimated plasma volume status (ePVS) and the prognosis of SAP remains elusive. This study was aimed at assessing the relationship of ePVS with the risk of 30-day all-cause mortality (ACM) in SAP patients. Methods This study collected clinical data on SAP patients in the ICU from the MIMIC-IV database. LASSO regression was used to screen for relevant covariates. The nonlinear relationship of ePVS with the risk of 30-day ACM was assessed utilizing the restricted cubic spline (RCS) analysis, and then their association was assessed by a multivariate Cox regression model. 30-day survival across different groups was compared by a Kaplan-Meier survival curve. Results This study included 1036 patients, with a 30-day survival rate of 86.8%. They were assigned to four groups by quartiles of ePVS. The Kaplan-Meier survival curve showed that the high ePVS group was at a higher risk of 30-day ACM (p = 0.007). Multivariate Cox regression analysis showed a positive association of ePVS as a continuous variable with the risk of 30-day ACM (HR = 1.09, 1.01–1.18, p = 0.035). The risk of 30-day ACM was higher in the Q4 group vs. the Q1 group with ePVS as a categorical variable (HR = 1.70, 95% CI: 1.03–2.80, p = 0.039). RCS analysis showed a linear relationship of ePVS with the risk of 30-day ACM (p = 0.606), with a cut-off value of 6.23 dL/g. Subgroup analysis revealed significant associations between the two within specific subgroups, but ePVS did not interact with any of the subgroup variables. Conclusion Our findings showed a significant association of high ePVS values with an increased risk of 30-day ACM. This study helps to identify high-risk patients early and guide the development of personalized treatment strategies.